BMP-2 modulates expression of other growth factors in a rat fracture healing model - Cttrell, Jessica Ann; Keane, Owen; Lin, Sheldon Sutton; O'Connor, James Patrick (Journal of Applied Biomedicine, 2014)
x
Keywords: exprese genu; Recombinant Proteins; Gene Expression; Research; RNA, Messenger; Bony Callus; kvantitativní polymerázová řetězová reakce; uzavřené fraktury; Bone Morphogenetic Protein 4; Fracture Healing; potkani Sprague-Dawley; Tumor Necrosis Factor-alpha; osteogeneze; fraktury femuru; kostní morfogenetický protein 4; kostní morfogenetické proteiny; kostní morfogenetický protein 7; regenerace kostí; Bone Morphogenetic Proteins; Femoral Fractures; stanovení celkové genové exprese; Real-Time Polymerase Chain Reaction; výzkum; Bone Morphogenetic Protein 2; Bone Morphogenetic Protein 6; Gene Expression Profiling; krysa rodu Rattus; rekombinantní proteiny; Time Factors; Bone Morphogenetic Protein 7; Intercellular Signaling Peptides and Proteins; Animals; ženské pohlaví; mezibuněčné signální peptidy a proteiny; kostní morfogenetický protein 6; Fractures, Closed; zvířata; Rats; časové faktory; TNF-alfa; kostní morfogenetický protein 2; kostní svalek; Osteogenesis; Bone Regeneration; Female; messenger RNA; hojení fraktur; Rats, Sprague-Dawley